Evaluation of Allostatic Load as a Marker of Chronic Stress in Children and the Importance of Excess Weight - Calcaterra, Valeria; Vinci, Federica; Casari, Giulia; Pelizzo, Gloria; de Silvestri, Annalisa; De Amici, Mara; Albertini, Riccardo; Regalbuto, Corrado; Montalbano, Chiara; Larizza, Daniela; Cena, Hellas (Frontiers in Pediatrics, 2019)
Introduction Allostatic load (AL) refers to the physiological response associated with the burden of chronic stress. Excessive weight is an important source of physiological stress that promotes a detrimental chronic low-inflammation state. In order to define a correlation between cumulative biological dysregulation and excess weight, we measured AL scores in a pediatric population. Patients and methods We enrolled 164 children and adolescents (11.89 ± 3.89). According to their body mass index (BMI) threshold, subjects were classified as normal for weight BMI<75th percentile, overweight BMI 75-95th percentile or obese BMI>95th percentile. Data based on 16 biomarkers were used to create the AL score. A dichotomous outcome for high AL was defined in those who had more than 4 dysregulated components. Results High AL was noted in 88/164 subjects (53.65%), without significant differences between genders (p =0.07) or pubertal status (p=0.10). Subjects with a high AL, in addition higher BMI (p<0.001), showed higher WC and WC/HtR (p<0.001), triglycerides (p=0.002), fasting blood glucose (p=0.03), insulin resistance (p<0.001), systolic (p<0.001) and diastolic blood pressure (p=0.001), GGT (p=0.01), PCR (p=0.01) and calprotectin (p<0.01) as well as lower HDL cholesterol (p=0.002) than subjects with a low AL. The rate of the cumulative biological dysregulation increased progressively with increases in BMI (p< 0.001). Conclusions A high AL was associated with excess weight. AL may be considered a significant factor correlated with increased morbidity in children who are overweight/obese.